2008
DOI: 10.1162/rest.90.4.792
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Representations of the Output Gap

Abstract: Methods are described for the appropriate use of data obtained and analysed in real time to represent the output gap. The methods employ cointegrating VAR techniques to model real time measures and realisations of output series jointly. The model is used to mitigate the impact of data revisions; to generate appropriate forecasts that can deliver economically-meaningful output trends and that can take into account the end-of-sample problems encountered in measuring these trends; and to calculate probability for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 28 publications
0
55
0
1
Order By: Relevance
“…Namely, we can expand the information set supplied to the filter by use of forecasts, a solution that has been proved successful in previous literature Maravall, 1999, 2001;Mise et al, 2005;Garratt et al, 2008). Under the same circunstances as in the original formulation, (1), suppose now we have h = 1, .., H forecasts of y T +h at our disposal 2 .…”
Section: Formulation and End-of-sample Inaccuracymentioning
confidence: 99%
See 1 more Smart Citation
“…Namely, we can expand the information set supplied to the filter by use of forecasts, a solution that has been proved successful in previous literature Maravall, 1999, 2001;Mise et al, 2005;Garratt et al, 2008). Under the same circunstances as in the original formulation, (1), suppose now we have h = 1, .., H forecasts of y T +h at our disposal 2 .…”
Section: Formulation and End-of-sample Inaccuracymentioning
confidence: 99%
“…The most prominent attempts involve expanding the information set supplied to the filter in the temporal dimension, using either model-based forecasts (Kaiser and Maravall, 1999;Gomez, 2001;Kaiser and Maravall, 2001;Mise et al, 2005), or variables observed at a higher frequency (Aruoba et al, 2009); in the covariates dimension with the employment of model-based multivariate representations (Planas and Rossi, 2004; Valle e Azevedo et al, 2006;Altissimo et al, 2010;Valle e Azevedo, 2011;Marcellino and Musso, 2011), or jointly in both of these dimensions (Garratt et al, 2008;Clements and Galvão, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Figure 5a describes the probability of the event HP (and other) filters in defining gaps and Orphanides and van Norden (2002) showed that these are typically very vulnerable to real-time analysis. However, Garratt et al (2008) showed that the method described above, applying smoothing techniques to forecast-augmented series, can considerably improve the precision of the estimates of an output gap at the end-of-sample. This is, of course, extremely important in realtime decision-making.…”
Section: Recession Defined Using the Output Gapmentioning
confidence: 99%
“…Subsequent papers have explored a variety of approaches to dealing with the uncertainty surrounding more mature estimates. Some, such as Patterson (1994) and Garratt, Lee, Mise, and Shields (2005), increase the number of releases in the model so that estimates are not assumed to become 'true' for two or three years. In the case of the United Kingdom's National Accounts, however, revisions have been applied to even more mature estimates.…”
Section: An Overview Of the Literaturementioning
confidence: 99%
“…One natural question is whether data-9 users should consider these previous releases as competing measures of the truth -that is, using y t+n−j t alongside y t+n t as measures of y t . In contrast with the treatment in much of the antecedent literature, we decide to exclude earlier releases from the set of measures used to estimate 'true' activity, see, for example, Garratt, Lee, Mise, and Shields (2005). The reason for using only the latest release is pragmatic.…”
Section: The Model For the True Datamentioning
confidence: 99%